Legal Analysis of The Implementation of Restorative Justice Principles In Police Services After The Effectiveness of Law Number 1 of 2023 Concerning The Criminal Code - Anyar Ayu Bening Wirya Cherdika; Mhd Azhali Siregar; T. Riza Zarzani (CV. Era Digital Nusantara, 2026)
The enactment of Law Number 1 of 2023 concerning the Criminal Code marks a paradigm shift in criminal law in Indonesia, no longer oriented toward retributive punishment but instead prioritizing a restorative approach through the principle of restorative justice. This change has implications for criminal law enforcement practices, particularly within the police service, which serves as the gateway to the criminal justice system. The application of restorative justice within the police is seen as an effort to provide a more humane and effective resolution of criminal cases, oriented toward restoring social relations between perpetrators, victims, and the community. However, its implementation still faces various normative and practical obstacles that have the potential to create legal uncertainty. This study aims to analyze the regulations and legal basis for the application of restorative justice principles in police services following the enactment of the 2023 Criminal Code and to examine the legal implications of its application on the effectiveness of criminal law enforcement in the North Sumatra Regional Police. The research method used is normative juridical, supported by empirical data through legislative, conceptual, and case approaches. Data was obtained through literature review, document review, and interviews with law enforcement officials regarding the implementation of restorative justice. The results indicate that normatively, the application of restorative justice has gained legal legitimacy through the 2023 Criminal Code, the Republic of Indonesia National Police Regulation Number 8 of 2021, and internal police policies. The implementation of restorative justice at the North Sumatra Regional Police has been applied to certain crimes through mediation and reconciliation between perpetrators and victims. However, in practice, obstacles remain, including the lack of uniform standard operating procedures, reliance on investigator discretion, and weak oversight. Therefore, regulatory strengthening, policy harmonization between law enforcement agencies, and increased police capacity are needed to realize a fair, effective, and accountable implementation of restorative justice.